ATTITUDE AND LEVEL OF PERFORMANCE OF STUDENTS IN CHEMISTRY - Malana, Matilde Lacambra (International Journal of Psychosocial Rehabilitation, 2020)
This study determined the attitude of students in chemistry. It further determined the relationship of their attitude to their performances in Math, Chemistry and English. There were 244 respondents in this study coming from select higher education institutions in Cagayan. This study made use of the descriptive- correlational method to describe the personal variables and attitude of the respondents. It is correlational since it also tried to determine if there is relationship in the attitude of students and their performance in Math, Chemistry and English by using the person product correlation. The researcher made use of the questionnaire to gather the data. It was found out that the attitude of students is significantly related to their performance in Chemistry which applied that students whose attitude is positive had better performance in the cognitive subjects. Consequently, those students who had negative attitude towards the cognitive subjects like chemistry performed lower in the subject. It is recommended by the researcher that Chemistry teachers should emphasize the difficult concepts and skills of cognition and that students must be taught “to be active strategic learner”. Analytical and critical approach to chemistry learning should be emphasized also in the classroom. Finally, teachers should device a strategy to develop positive attitude towards chemistry that would likely result to achieving better performance.